Intraoperative goal directed hemodynamic therapy in noncardiac surgery: a systematic review and meta-analysis - Javier Ripollés; Angel Espinosa; Eugenio Martínez-Hurtado; Alfredo Abad-Gurumeta; Rubén Casans-Francés; Cristina Fernández-Pérez; Francisco López-Timoneda; José María Calvo-Vecino (Brazilian Journal of Anesthesiology, 2016)
Background: The goal directed hemodynamic therapy is an approach focused on the use of cardiac output and related parameters as end-points for fluids and drugs to optimize tissue perfusion and oxygen delivery. Primary aim: To determine the effects of intraoperative goal directed hemodynamic therapy on postoperative complications rates. Methods: A meta-analysis was carried out of the effects of goal directed hemodynamic therapy in adult noncardiac surgery on postoperative complications and mortality using Preferred Reporting Items for Systematic Reviews and Meta-Analyses methodology. A systematic search was performed in Medline PubMed, Embase, and the Cochrane Library (last update, October 2014). Inclusion criteria were randomized clinical trials in which intraoperative goal directed hemodynamic therapy was compared to conventional fluid management in noncardiac surgery. Exclusion criteria were trauma and pediatric surgery studies and that using pulmonary artery catheter. End-points were postoperative complications (primary) and mortality (secondary). Those studies that fulfilled the entry criteria were examined in full and subjected to quantifiable analysis, predefined subgroup analysis (stratified by type of monitor, therapy, and hemodynamic goal), and predefined sensitivity analysis. Results: 51 RCTs were initially identified, 24 fulfilling the inclusion criteria. 5 randomized clinical trials were added by manual search, resulting in 29 randomized clinical trials in the final analysis, including 2654 patients. A significant reduction in complications for goal directed hemodynamic therapy was observed (RR: 0.70, 95% CI: 0.62–0.79, p < 0.001). No significant decrease in mortality was achieved (RR: 0.76, 95% CI: 0.45–1.28, p = 0.30). Quality sensitive analyses confirmed the main overall results. Conclusions: Intraoperative goal directed hemodynamic therapy with minimally invasive monitoring decreases postoperative complications in noncardiac surgery, although it was not able to show a significant decrease in mortality rate. Resumo: Justificativa: A terapia hemodinâmica alvo-dirigida (THAD) é uma abordagem focada no uso do débito cardíaco (DC) e parâmetros relacionados, como desfechos para fluidos e medicamentos para otimizar a perfusão tecidual e o fornecimento de oxigênio. Objetivo primário: determinar os efeitos da THAD sobre as taxas de complicações no pós-operatório. Métodos: Meta-análise dos efeitos da THAD em cirurgias não cardíacas de adultos sobre as complicações pós-operatórias e mortalidade, usando a metodologia PRISMA. Uma busca sistemática foi realizada no Medline PubMed, Embase e Biblioteca Cochrane (última atualização, outubro de 2014). Os critérios de inclusão foram estudos clínicos randômicos (ECRs) nos quais a THAD no intraoperatório foi comparada com a terapia convencional de reposição de líquidos em cirurgia não cardíaca. Os critérios de exclusão foram traumatismo e estudos de cirurgia pediátrica e aqueles usando cateter de artéria pulmonar. Os desfechos, primário e secundário, foram complicações pós-operatórias e mortalidade, respectivamente. Os estudos que atenderam aos critérios de inclusão foram examinados na íntegra e submetidos à análise quantitativa, análise de subgrupo pré-definido (estratificada por tipo de monitor, terapia e objetivo hemodinâmico) e análise de sensibilidade pré-definida. Resultados: 51 ECRs foram identificados inicialmente, 24 atenderam aos critérios de inclusão. Cinco ECRs foram adicionados por busca manual, resultando em 29 ECRs para análise final, incluindo 2.654 pacientes. Uma redução significativa das complicações para a THAD (RR: 0,70, IC de 95%: 0,62-0,79, p < 0,001). Nenhuma diminuição significativa na mortalidade foi observada (RR: 0,76, IC de 95%: 0,45-1,28, p = 0,30). Análises de sensibilidade qualitativa confirmaram os principais resultados gerais. Conclusões: THAD no intraoperatório com monitoração minimamente invasiva diminui as complicações no pós-operatório de cirurgia não cardíaca, embora não tenha mostrado uma redução significativa da taxa de mortalidade. Keywords: Goal directed fluid therapy, Meta-analysis, Hemodynamic goal, Noncardiac surgery, Palavras-chave: Fluidoterapia alvo-dirigida, Metaanálise, Objetivo hemodinâmico, Cirurgia não cardíaca